The New Map : Energy, Climate, and the Clash of Nations - Yergin, Daniel (UK Penguin Books, 2021)
"Recent changes in the global production and flow of energy have remade the world. In this book, the author reveals the forces shaping the future of energy, both renewable and fossil fuel. The New Map offers a new vision of the world's energy reserves and, therefore, the future of geopolitics"-- Provided by publisher
Include Illustrations and Index
Keywords: Renewable energy sources -- Climatic changes--Economic aspects -- International relations -- Geopolitics